Internal control proposal for municipalities based on the survey and analysis of second category municipalities in the province of Misiones - Ana Maria Czubarski; Letizia Mariel Paprocki; Alejandra María Lorena Ramírez; Mariana Villamayor Nercolini (Visión de Futuro, 2023)
Currently, municipalities are in a stage of institutional strengthening addressing different tools to improve their management. Although they advance in different topics, in general they focus on aspects of legality control aimed to comply the required rendering of accounts. A good internal control implementation would contribute to an improvement in management, presenting benefits both for these organizations and for the citizenship. This article intends to address the current situation of internal control in small municipalities, from the survey and analysis of the second category municipalities of the province of Misiones, Argentina, in order to know through quiz of municipal accountants, what activities are carried out in this area and carry out an analysis of different aspects that could be improved in the light of good practices of this type of control. These municipalities are taken as the unit of analysis since, being small and having a reduced administrative structure, they allow us to know the reality of the small municipalities of the country, the conclusions being applicable to the latter.